Penerapan Tanggung Jawab Sosial Perusahaan pada Perusahaan dibidang Pertambangan di Kabupaten Karimun - Elza Syarief; Asmin Patros; Naomi Hani Romauli Simanungkalit (Journal of Judicial Review, 2014)
Any company run their business activities in the filed and related to the natural resoucers filed is required to conduct the environmental and social responsibility. Particulary the Natural resoucers explotations done by mining companies often causing the environment degradation and by not giving any attention to the social aspects at the surrounding of the company. This research is using the Law of Social Research Methods.Result and discussion. Social responsibility and environmenttal implementation will be applied properly if the government and the social and environmental responsibility program are done in synergies, and the funds can be an alternative for financing the program in support of the non budgeting financing. The conclusion is, government regulation no 47 year 2012 has been implemented in Kabupaten Karimun by using the concept of community development. Suggestion is to done the revision for the government regulation no 47 year 2012 to regulate and reinformce the provisions on the sanctions, establish regulations applicable in general, and to form the local government regulation or PERDA governing the social and environmental responsibility that suit to local needs at Kabupaten Karimun.